2016
DOI: 10.1002/erv.2475
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Clinical Effect of High‐frequency rTMS to Dorsolateral Prefrontal Cortex on Bulimic Symptoms: A Randomised, Double‐blind Trial

Abstract: Studies suggest that stimulation of the left dorsolateral prefrontal cortex (DLPFC) reduces food craving in bulimic patients, but evidence supporting repetitive transcranial magnetic stimulation (rTMS) as a therapeutic tool is lacking. We investigated the safety and therapeutic efficacy of an adjunct high-frequency rTMS programme targeting the left DLPFC. Forty-seven women with bulimia nervosa were randomised to a real or sham stimulation group. The real group underwent 10 rTMS sessions, each consisting of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 59 publications
1
43
0
4
Order By: Relevance
“…Last, there were no correlations between IGT and inhibitory control performances and no correlations between neuropsychological performances and clinical variables (number of binge episodes and vomiting episodes, impulse regulation level and bulimia symptom levels). (Gay et al, 2016). Similar results were found for people with alcohol dependence (Del Felice et al, 2016), with HF rTMS over the left DLPFC improving performance of a cognitive inhibition control task but ineffective at reducing alcohol intake.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Last, there were no correlations between IGT and inhibitory control performances and no correlations between neuropsychological performances and clinical variables (number of binge episodes and vomiting episodes, impulse regulation level and bulimia symptom levels). (Gay et al, 2016). Similar results were found for people with alcohol dependence (Del Felice et al, 2016), with HF rTMS over the left DLPFC improving performance of a cognitive inhibition control task but ineffective at reducing alcohol intake.…”
Section: Resultssupporting
confidence: 64%
“…Nevertheless, despite improvement in decision‐making and inhibitory control in our sample, rTMS had no benefit over placebo regarding bulimic symptoms (number of binges, length of the longest binge episode, features of the binge episodes, etc.) (Gay et al, ). Similar results were found for people with alcohol dependence (Del Felice et al, ), with HF rTMS over the left DLPFC improving performance of a cognitive inhibition control task but ineffective at reducing alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a single session of tDCS of the dorsolateral PFC reduced urges to binge in 39 patients with BN [99], while a similarly designed study reported reduction in urges to binge in 30 patients with BED [100]. Several preliminary studies of women with BN suggested that rTMS of the left dorsolateral PFC [101][102][103] and dorsomedial PFC [104] reduced food cravings, but a randomized doubleblinded study of 47 women with BN found no clinical benefit of rTMS to the left dorsolateral PFC [105].…”
Section: Neuromodulationmentioning
confidence: 99%
“…One important feature of this model is that it does not require forced calorie restriction or stress to induce the bingelike episodes. This model has identified several potential novel therapies, including DBS of the nucleus accumbens [112,113], the serotonin 2C receptor agonist lorcaserin [105], and the nociceptin receptor antagonist LY2940094 [114].…”
Section: Preclinical Models Of Binge-like Eatingmentioning
confidence: 99%
“…Single sessions of tDCS or repetitive TMS (rTMS) to the dlPFC have been reported to improve symptoms in BN and AN patients (Kekic et al, 2017;Van den Eynde, Guillaume, Broadbent, Campbell, & Schmidt, 2013). However, clinical trials applying multi-session tDCS or rTMS protocols to the dlPFC yielded inconsistent findings (Gay et al, 2016;Khedr, Elfetoh, Ali, & Noamany, 2014;McClelland, Kekic, Campbell, & Schmidt, 2016). On the other hand, improvements in binge-purge behavior have been reported applying rTMS to the mPFC (Dunlop et al, 2015).…”
mentioning
confidence: 99%